Lumboperitoneal shunt surgery via continuous two-stage procedure: Technique notes and outcomes - Li, Zhao; Wang, Hao; Zhang, Han; Yang, Jiqi; Yang, Xiaofeng; Wen, Liang (Frontiers in Neurology, 2022)
Background Lumboperitoneal shunt (LPS) is an effective procedure for managing communicating hydrocephalus. LPS is performed as a one-stage procedure with the patient placed in the lateral position or as a two-stage procedure in which the patient's position is changed. Both methods can be bothersome to neurosurgeons. We designed a continuous two-stage LPS procedure in which the operative sites did not need to be sterilized again, and the surgical drapes did not have to be changed after changing the patient's position. In this study, we analyzed this procedure in terms of the technical features and outcomes. Methods All patients from our institute who underwent LPS using the continuous two-stage procedure from October 2019 to August 2021 were reviewed retrospectively. The patient's demographic information, clinical features, operative data, and outcomes were analyzed. Results A total of 46 consecutive patients who underwent LPS using the continuous two-stage procedure were enrolled. The mean operative duration was 70.6 ± 12.7 min. The 180-day revision rate for these patients was 2.2% (1/46). Moreover, 76.1% of the patients (35/46) experienced clinical improvement after LPS during the 180-day follow-up, and 70.0% of the patients (32/46) experienced an improvement in neuroimaging. Conclusion We described a continuous two-stage LPS procedure. This method simplified the two-stage LPS procedure and maintained a low malfunction rate and shunt infection rate in our series.